The Influence of Practical Drawing Courses on Student Work Competence in SKKNI Building Drawing: Case Study at Surabaya State University - Soeparno, Soeparno; Suparji, Suparji; Wiyono, Agus; Hidayati, Lutfiyah; Baskoro, Farid (East Asian Journal of Multidisciplinary Research, 2024)
This research examines the influence of emphasizing practical drawing learning methods and work competencies in the SKKNI for building drawings. The majority of respondents work in the vocational school sector with a percentage of 53%. Furthermore, as many as 41% of respondents work in the PT sector. Meanwhile, only 6% of respondents work in the high school sector. The results of the analysis show that the majority of respondents consider these two methods to have a significant impact. The emphasis on "Fieldwork" was considered very large by 40 respondents and had a large influence by another 35 respondents, while "Participation in Research Projects" was considered very large by 25 respondents and had a large influence by 40 respondents. These findings emphasize the importance of practical learning methods and research projects in preparing graduates for various career paths, and demonstrate the variety of career choices made by graduates after completing their studies.